ChemInform Abstract: 2‐Chloro‐4‐tetrafluorophenoxypyrimidine: A Versatile Reagent for C‐2 Prior to C‐4 Functionalizations. Issue 32 (22nd July 2016) - O'Donnell, Michael; Charrier, Jean‐Damien
Abstract: 2, 4‐Substituted pyrimidines are prepared by C‐2 functionalization of 2‐chloro‐4‐tetrafluorophenoxypyrimidine (I) by cross‐coupling reactions followed by SN Ar displacement at C‐4 position with a variety of amines.